(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mangroves are most important to produce many valuable products, and plays important role in ecological functions that support coastal ecosystem. Due to the unsustainable utilization, Indian mangrove resources being lost. Xylocarpus granatum is a mangrove species that has medicinal properties and declared as critically endangered plant for the Maharashtra state. In present study, proximate composition of seeds of the species was investigated. The results revealed that, seeds of X. granatum are a richest resource of energy.